2019
DOI: 10.1016/j.scitotenv.2019.133845
|View full text |Cite
|
Sign up to set email alerts
|

Direct seeding for rice production increased soil erosion and phosphorus runoff losses in subtropical China

Abstract: Estimating soil erosion and nutrient losses from surface runoff in paddy fields is essential for the assessment of sustainable rice (Oryza sativa L.) production and water quality protection. Different rice establishment methods have been used in the last three decades in Asia; however, it is still unclear how these methods influence sustainable agriculture and environmental protection in humid areas. The aim of this study was to evaluate the impacts of rice establishment method on soil erosion and phosphorus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Some small-scale in-situ experiments showed that total P (TP) runoff losses ranged from 0.18 to 1.51 kg ha −1 and PP runoff losses accounted for 58%-77% of the seasonal TP lost. They further revealed that nutrient loss loading varied with seasons [12].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Some small-scale in-situ experiments showed that total P (TP) runoff losses ranged from 0.18 to 1.51 kg ha −1 and PP runoff losses accounted for 58%-77% of the seasonal TP lost. They further revealed that nutrient loss loading varied with seasons [12].…”
mentioning
confidence: 96%
“…Nitrogen and phosphorus losses from paddy fields usually occur predominantly through surface runoff rather than infiltration because of a plow pan that prevents downward water infiltration [11]. Some studies have shown that N and P runoff losses are affected by soil and climatic parameters, as well as agricultural practices, including soil texture, cover crops, application rate of N and P fertilizers, timing and method, soil tillage, irrigation regimes, and rainfall intensity and amount [12][13][14]. Some small-scale in-situ experiments showed that total P (TP) runoff losses ranged from 0.18 to 1.51 kg ha −1 and PP runoff losses accounted for 58%-77% of the seasonal TP lost.…”
mentioning
confidence: 99%
“…Nitrogen and phosphorus losses from paddy fields usually occur predominantly through surface runoff rather than infiltration because of a plow pan that prevents downward water infiltration [13]. Some studies have shown that N and P runoff losses are affected by soil and climatic parameters, as well as agricultural practices, including soil texture, cover crops, the application rate of N and P fertilizers, timing and method, soil tillage, irrigation regimes, and rainfall intensity and amount [14][15][16]. A smallscale in-situ experiment show that total P (TP) runoff losses ranged from 0.18 to 1.51 kg ha −1 , and particulate P (PP) runoff losses accounted for 58-77% of the seasonal TP lost [14].…”
mentioning
confidence: 99%
“…Some studies have shown that N and P runoff losses are affected by soil and climatic parameters, as well as agricultural practices, including soil texture, cover crops, the application rate of N and P fertilizers, timing and method, soil tillage, irrigation regimes, and rainfall intensity and amount [14][15][16]. A smallscale in-situ experiment show that total P (TP) runoff losses ranged from 0.18 to 1.51 kg ha −1 , and particulate P (PP) runoff losses accounted for 58-77% of the seasonal TP lost [14]. They further reveal that nutrient loss loading varied with seasons [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation